O uso de telas na rotina de crianças pré-escolares no Transtorno do Espectro Autista (TEA) e suas repercussões no brincar - Gomes, Ana Beatriz dos Santos (Universidade Federal de São Carlos, 2026)
Introduction: Play is the primary occupation of childhood, being fundamental to the cognitive, motor, and psychosocial development of children. However, the replacement of play with screen-mediated activities has raised concerns among health professionals, considering that this reality, when associated with an Autism Spectrum Disorder (ASD) diagnosis, can exacerbate issues related to attention, language, motor coordination, and social interaction. Therefore, it is necessary to investigate the repercussions of this situation on the play of this population. Objective: To investigate the use of screens in the daily routines of children diagnosed with Autism Spectrum Disorder (ASD) aged 2 to 5 years and 11 months, and how this impacts their play. Method: A descriptive-exploratory study with a quantitative and qualitative approach, involving the administration of a semi-structured questionnaire to parents/guardians. Quantitative data will be analyzed using descriptive statistics and correlational analysis. Qualitative data will be analyzed through content analysis, with responses being categorized and interpreted to identify patterns. Results: The results indicate an early introduction to and intense use of screens, with a significant portion of the children exceeding three hours of daily use. It is observed that device usage frequently replaces traditional play and influences play activities. Furthermore, caregivers present ambivalent perceptions: they acknowledge some benefits but highlight negative behavioral and emotional impacts. Moreover, the analysis evidenced that high screen time is intrinsically linked to caregiver burden (predominantly mothers), acting as a survival and organizational tool in the face of household routine demands and the scarcity of structured support networks.
The use of screens in the routine of preschool children with Autism Spectrum Disorder (ASD) and its repercussions on play
Keywords: Dispositivos Móveis; Brincar; Transtorno do Espectro Autista; Desvios do Desenvolvimento Infantil; Terapia Ocupacional; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar